2004
DOI: 10.1038/sj.onc.1207648
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 is required for Akata6 B-lymphoma cell survival and is converted to a cell death molecule by efficient caspase-mediated cleavage

Abstract: Enforced expression of the antiapoptotic Bcl-2 family protein Mcl-1 promotes lymphomagenesis in the mouse; however, the functional role of Mcl-1 in human B-cell lymphoma remains unclear. We demonstrate that Mcl-1 is widely expressed in malignant B-cells, and high-level expression of Mcl-1 is required for B-lymphoma cell survival, since transfection of Mcl-1-specific antisense oligodeoxynucleotides was sufficient to promote apoptosis in Akata6 lymphoma cells. Mcl-1 was efficiently cleaved by caspases at evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(155 citation statements)
references
References 48 publications
8
144
1
1
Order By: Relevance
“…8 In dying cells, MCL-1 can be eliminated by caspase-mediated cleavage generating a potent proapoptotic protein that can enhance the cell death response. 9 These findings demonstrate that MCL-1 is tightly regulated at several levels, but it remains to be established what the physiological regulation of MCL-1 is during normal development and homeostasis.…”
mentioning
confidence: 84%
“…8 In dying cells, MCL-1 can be eliminated by caspase-mediated cleavage generating a potent proapoptotic protein that can enhance the cell death response. 9 These findings demonstrate that MCL-1 is tightly regulated at several levels, but it remains to be established what the physiological regulation of MCL-1 is during normal development and homeostasis.…”
mentioning
confidence: 84%
“…Because a high level of MCL1 was shown to mediate resistance to fludarabine in vivo and in vitro, 28,29 abrogation of MCL1 by PEITC likely facilitated the killing of F-ara-A-refractory CLL cells. As MCL1 may be a better substrate for caspase than BCL2, 30 we used the pan-caspase inhibitor Z-VAD-fmk to test if it could prevent PEITC-induced MCL1 degradation, and showed that the 20 M Z-VAD-fmk largely suppressed MCL1 degradation in PEITC-treated cells ( Figure 6C). Similar effect was observed by using the specific inhibitor to caspase-3, Z-DEVD (data not shown), suggesting that caspase-3 might be a major protease that cleaved MCL1.…”
Section: Induction Of Rapid Degradation Of the Antiapoptotic Protein mentioning
confidence: 99%
“…Several members of the Bcl-2 protein family display protease cleavage sites, and their cleavage products have been shown in general to enhance apoptotic activity (Cheng et al, 1997;Clem et al, 1998;Fujita et al, 1998;Wood et al, 1998;Condorelli et al, 2001;Michels et al, 2004) and in some cases to mediate apoptotic activity (Ofengeim et al, 2012). Sequence comparison between human, canine and murine Bcl-2 family members has revealed a number of fully conserved cleavage sites.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the comparative tetramer sequences preceding cleavage sites reported in the literature. Sequences 100% conserved in all three species include both caspase-3 cleavage sites of Bcl-xL, the major caspase-3 cleavage sites of Mcl-1 and of Bad, and the calpain recognition sequence of Bax (Cheng et al, 1997;Clem et al, 1998;Fujita et al, 1998;Wood et al, 1998;Condorelli et al, 2001;Michels et al, 2004).…”
Section: Protein Sequence Comparison Of Canine Bcl-2 Family Members Wmentioning
confidence: 99%